Measuring Students' Scientific Argumentation Skills in Explaining Phenomena Related to Acid-Base Concepts - Rahmawati Hilala; Lukman Abdul Rauf Laliyo*; Jafar La Kilo; Julhim S. Tangio; Erni Mohamad; Mangara Sihaloho (Jurnal Pendidikan Sains Indonesia, 2023)
Scientific argumentation is one of the main competencies of students in communicating chemical phenomena through the application of conceptual mastery that they have understood. The development of this ability has been postulated in the 2013 curriculum through constructivist-based learning approaches and scientific inquiry, either in the classroom or the laboratory. However, there is relatively little information on how students' scientific argumentation skills develop. This study aims to measure students' scientific argumentation skills in explaining five science phenomena related to the acid-base concept, namely: acid rain, salt crystal making, the use of antacids as ulcer medicine, the use of CaMgCO3 dolomite fertilizer, and the difference in the acidity level of HCl and H2SO4, using Rasch modeling. Each phenomenon was measured by three multiple-choice test items, which were developed to test students' ability to make claims (Q1), evidence (Q2), and justification (Q3). The data were analyzed using Rasch modeling, allowing researchers to measure the item and individual respondent levels. Respondents were 100 chemistry students in Gorontalo, who were differentiated in gender and adversity quotient. The results showed that the measurement instrument has good validity and reliability. In addition, it was found that students' abilities differed; some items responded differently regarding gender and adversity quotient. Most students tended to be weak in explaining the phenomenon of acid rain, the use of antacids for ulcer disease, the use of dolomite fertilizer, and the difference in the acidity level of HCl and H2SO4